Importin α/β mediates nuclear import of individual SUMO E1 subunits and of the holo-enzyme - Moutty, Marie Christine; Sakin, Volkan; Melchior, Frauke (Molecular biology of the cell, 2011)
SUMOylation, reversible attachment of small ubiquitin-related modifier (SUMO), serves to regulate hundreds of proteins. Consistent with predominantly nuclear targets, enzymes required for attachment and removal of SUMO are highly enriched in this compartment. This is true also for the first enzyme of the SUMOylation cascade, the SUMO E1 enzyme heterodimer, Aos1/Uba2 (SAE1/SAE2). This essential enzyme serves to activate SUMO and to transfer it to the E2-conjugating enzyme Ubc9. Although the last 40 amino acids in yeast Uba2 have been implicated in its nuclear localization, little was known about the import pathways of Aos1, Uba2, and/or of the assembled E1 heterodimer. Here we show that the mammalian E1 subunits can be imported separately, identify nuclear localization signals (NLSs) in Aos1 and in Uba2, and demonstrate that their import is mediated by importin α/β in vitro and in intact cells. Once assembled into a stable heterodimer, the E1 enzyme can still be efficiently imported by importin α/β, due to the Uba2 NLS that is still accessible. These pathways may serve distinct purposes: import of nascent subunits prior to assembly and reimport of stable E1 enzyme complex after mitosis.
Gesehen am 08.09.2022